Understanding Bird Preference on Agroforestry System: Is There a Potential Case for Birdwatching Development? - Agung Sih Kurnianto; Jati Batoro; Nia Kurniawan (Journal of Indonesian Tourism and Development Studies, 2017)
The main objective of this study is to understand the bird preference on the different types of agroforestry management and the implication on the development of birdwatching as a potential ecotourism. The study was conducted at the agroforestry area of Gubugklakah Village, Malang Regency, East Java Province, Indonesia, from May to November 2016. Five observation sites were chosen: 1) agroforestry developed by ethno-conserving system; 2) agroforestry close to the national park; 3) agroforestry; 4) conventional agriculture area; and 5) houses area. Point Count was applied in this study by determining 5 sampling sites that separated 100-150 m. Survey was conducted once a week and observed every 15 minutes from 6.00 to 9.00 am. The species of bird that observed and heard were noted, identified and result of the field identification was stored in field book. The result shows that the highest Importance Value Index (IVI) was presented by Cave swiftlet and some species that specialized in farmland. Agroforestry area was showing more potential as the birdwatching spot compared to conventional agriculture area and houses area. In addition, agroforestry area showing a high Value of Interest (VOI) that represented a nativity on the birds settler and made it to be the suitable area for birdwatching activities.Keywords: agroforestry, birdwatching, management, preference.